Laporan Non-Keuangan pada Organisasi Sektor Publik: Laporan Terintegrasi, Laporan Keberlanjutan, Laporan Populer, dan Pengungkapan Berbasis Web - Gisilowati Dian Purnamasari; Indah Murni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This systematic literature review aims to identify key trends and research gaps in non-financial reporting formats: Integrated Reporting (IR), Sustainability Reporting (SR), Popular Reporting (PR), and Web-Based Disclosure (WD) within public sector organizations. The study analyzed 113 articles published between 2020 and 2025 from Google Scholar, Web of Science, and Scopus, supported by keyword co-occurrence analysis and WordCloud visualizations using VosViewer. The findings reveal that IR and SR dominate the public sector non-financial reporting literature and have grown steadily since 2015, playing a pivotal role in fostering integrated thinking, accountability, and socio-environmental transparency. In contrast, PR and WD remain relatively underexplored. Key challenges include limited knowledge, regulatory gaps, and human resource constraints, while emerging innovations involve metaverse-based reporting and digital forensics. Geographically, research is concentrated in Europe. The study’s limitations lie in its focus on recent literature, predominantly from Europe. Future research should broaden coverage of PR/WD, conduct longitudinal analyses, assess the impact of reporting on stakeholder decision-making, and develop more accessible digital platforms. Practically, policymakers should enhance transparency through clear regulations and training, while organizations should prioritize stakeholder engagement and integrated information. This review systematically maps trends and gaps, contributes to a conceptual framework, and offers practical insights to strengthen transparency and accountability in public administration.